1998
DOI: 10.1128/jvi.72.8.6298-6306.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Porcine Reproductive and Respiratory Syndrome Virus GP 3 Glycoprotein Is Released into the Culture Medium of Cells as a Non-Virion-Associated and Membrane-Free (Soluble) Form

Abstract: The GP3 protein of the IAF-Klop strain of porcine reproductive and respiratory syndrome virus (PRRSV) was expressed in 293 cells by a recombinant human type 5 adenovirus carrying the open reading frame 3 gene. The protein exhibited a molecular mass of 42 kDa and comigrated with GP3 expressed in PRRSV-infected MARC-145 cells. Removal of N-linked glycans from GP3resulted in a 27-kDa protein (P3), confirming its highly glycosylated nature. Pulse-chase experiments carried out either in the context of PRRSV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…GP5 is the most abundant glycoprotein found on the surface of the virion and hence is named the major envelope glycoprotein, whereas the GP2a, GP3, and GP4 proteins, which are also present on the surface of the virion in less abundant quantities, are termed the minor envelope glycoproteins. Although early studies reported that the GP3 protein is not a structural component of the North American (genotype II) PRRS virions (24,34), recent studies from our laboratory have shown that it is present on the virion envelope (10), an observation consistent with the European (genotype I) PRRS virions (49). All of the major and minor envelope proteins are required for generation of infectious PRRSV (53).…”
supporting
confidence: 60%
“…GP5 is the most abundant glycoprotein found on the surface of the virion and hence is named the major envelope glycoprotein, whereas the GP2a, GP3, and GP4 proteins, which are also present on the surface of the virion in less abundant quantities, are termed the minor envelope glycoproteins. Although early studies reported that the GP3 protein is not a structural component of the North American (genotype II) PRRS virions (24,34), recent studies from our laboratory have shown that it is present on the virion envelope (10), an observation consistent with the European (genotype I) PRRS virions (49). All of the major and minor envelope proteins are required for generation of infectious PRRSV (53).…”
supporting
confidence: 60%
“…In contrast, for the PRRSV IAF-Klop strain, the GP 3 protein was characterized as nonstructural. Upon individual expression, as well as in the context of a PRRSV infection, a small fraction of the IAF-Klop GP 3 protein was shown to be secreted into the extracellular medium but the protein could not be identified in virions (20,31). For LDV, in vitro transcription and translation studies revealed that the ORF3-encoded protein was soluble or weakly associated with membranes through an uncleaved signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lelystad strain of PRRSV, it was found that their products (designated GP 4 and GP 3 , respectively) are minor glycoproteins of the virus (47). In contrast, the ORF3-encoded protein of the Quebec strain of PRRSV (IAF-Klop) has been shown to code for a soluble nonstructural protein (20,31). In vitro translation experiments showed that the ORF3-encoded protein of LDV is also a soluble protein (14).…”
mentioning
confidence: 99%
“…Some GP3 protein is secreted into the cell medium during PRRSV type 2 infections Mardassi et al, 1998;Wierenga et al, 2002) and it was initially thought not to be a structural protein. However, GP3 was subsequently identified as a minor component in both type 1 and 2 viruses (de Lima et al, 2009;van Nieuwstadt et al, 1996;Wissink et al, 2005).…”
Section: The Minor Envelope Proteinsmentioning
confidence: 99%